Assessing the Reliability and Validity of Television and Game Violence Exposure Measures. (February 2017) - Fikkers, Karin M.; Piotrowski, Jessica Taylor; Valkenburg, Patti M.
This study evaluated whether common self-report measures of television and game violence exposure represent reliable and valid measurement tools. Three self-report measures—direct estimates, user-rated favorites, and agency-rated favorites—were assessed in terms of test-retest reliability, criterion validity (their relationship with coded media diaries), and construct validity (their relationship with aggression and gender). A total of 238 adolescents participated in a two-wave survey and completed two media diaries. For game violence, the three self-report measures were reliable and valid. For television violence, only direct estimates achieved test-retest reliability and construct validity. Criterion validity could not be established for the television violence measures because the media diary was not a valid criterion for television violence. Our findings indicate that both direct estimates and favorites are valid measures for game violence, whereas for television violence, only direct estimates are valid. We conclude with a discussion about ways to further improve upon and reconceptualize media violence exposure measurement.